Eficiencia en la remoción de materia orgánica mediante lombrifiltros (Eisenia foetida) en aguas residuales domésticas para zonas rurales - Castillo Sánchez, Jonathan Gustavo (2021)
The inadequate management of domestic wastewater in rural areas, whose discharge to water bodies without prior treatment, is a major problem of environmental pollution, as well as a risk to public health. The purpose of this study was to evaluate the efficiency of organic matter removal by earthworms in domestic wastewater for rural areas. Under experimental conditions, the wormfilter was designed using as a theoretical basis the Tohá treatment system, created by Dr. José Tohá, which consisted of four strata: sawdaught + Eisenia foetida, activated charcoal, gravel and river stones. The experiment was carried out under an ACD using the InfoStat software, where three treatments with three repetitions each were proposed, thus generating 9 experimental units. The concentration of organic matter and volume of domestic wastewater in a home was evaluated, obtaining an estimated flow rate of 5,183ay⁄ and high concentrations of BOD5, COD, TSS and TS. Statistical analysis found that there are no significant differences in the removal of organic matter (p>0,05). However, T1 achieved the highest efficiency percentages with a volumetric flow of 1,8×10-2 l/s and TRH of 0,92 h obtaining 52,25 % for BOD5 and COD, 66,74 % TSS and 52,91 % TS, for which the hypothesis is accepted. Finally, a cost-benefit analysis determined that the implementation of wormfilters is low investment cost, thus affirming their application in the treatment of domestic wastewater in rural areas.